COMMUNITY SERVICE REPORT: ANIMAL POPULATION SURVEY AND IDENTIFICATION OF SOCIO-ECONOMIC CHALLENGES IN BATUAN KALER VILLAGE, SUKAWATI DISTRICT, GIANYAR - Yudha Yaksa Crada Yoga Arum Raharjo; Laurensius Arvel Wihangga; I Gusti Ayu Agung Candra Sari Dewi; Ni Nengah Indra Pradnya Darmayanti; Ida Ayu Metta Saraswati Sidemen; I Gusti Ngurah Sudisma; I Wayan Suardana; I Made Kardena; I Gusti Agung Adi Narayana (Buletin Veteriner Udayana, 2026)
Batuan Kaler Village in Gianyar, Bali, exhibits close communitarian interactions between the local community, domestic animals, and livestock. However, the absence of valid population demographic data and animal health status mapping often hinders the effectiveness of veterinary intervention programs and sectoral development in rural communities. This community service activity, conducted through the XXXVIII Veterinary Clinical Work (KKV), utilized a door-to-door census survey method across four banjars (traditional neighborhood/community unit in Bali) (Sakah, Dauh Uma, Cangi, and Blahtanah) to collect data on animal populations, dominant clinical complaints, and socio-economic constraints of the residents. The census recorded a total domestic animal population dominated by poultry/chickens (488 heads) and dogs (249 heads), while pig ownership was completely absent (0 heads). The most pervasive clinical complaints across all banjars were ectoparasite-induced skin diseases (pruritus, ticks, and hair loss) alongside low dog sterilization rates. Sectorally, residents faced challenges including rodent pest infestations and weather fluctuations in agriculture, manure accumulation issues in livestock management, as well as capital instability and declining tourist visits in the craft and trade sectors. This community service has successfully established a crucial database for veterinary management in Batuan Kaler Village. Integrated follow-up programs are urgently required, focusing on mass skin disease treatment, dog sterilization, and training on transforming livestock waste into organic compost (eco-farming) to sustain the economic resilience of the local community.